Pemikiran Ekonomi Abu Ishaq Al-Syatibi - Nurhidayah Nurhidayah; Fitri Hayati; Maysa Chairani; Miratul Imaniah; Aulia Syahfitri (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study employs a literature review and qualitative method to explore and analyze the economic thought of Abu Ishaq al-Shatibi, a prominent classical Islamic scholar known for his seminal work Al-Muwafaqat fi Usul al-Shari’ah. The research begins by examining his profile, including a brief biography, social background, and the intellectual environment that shaped his ideas. It further investigates his educational journey and leadership within the scholarly landscape of Andalusia. His core economic ideas, particularly related to the principles of maslahah (public interest) and maqasid al-shariah (objectives of Islamic law), are discussed as foundational frameworks for constructing a justice-based Islamic economic system. The study also explores the impact of al-Shatibi’s thought on social and fiscal policies during his era, emphasizing the strategic role of scholars in guiding moral and normative aspects of the economy. Ultimately, this research highlights the contemporary relevance of al-Shatibi’s ideas in addressing modern economic challenges, especially in terms of wealth distribution and protecting public rights within the structure of today’s economic systems.